2021
DOI: 10.1039/d1ce00129a
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and energetic characteristics of Se⋯Se interactions in crystal structures of organoselenium molecules

Abstract: Non-covalent selenium-selenium interactions between selenium-containing organic molecules were studied in crystal structures from the Cambridge Structural Database and by high-level quantum chemical calculations. Se…Se contacts in crystal structures were analyzed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Nevertheless, selenophene-based PBTSDPP exhibits a much larger L π of 38.51 Å than thiophene-based PBTTDPP with an L π of 18.01 Å, which can be attributed to the stronger Se−Se or Se−π interactions induced by the BTS units in PBTSDPP. 72,73 Larger L π from PBTSDPP yields a smaller R L , which leads to favorable edgeon orientation. Meanwhile, the smaller L π from PBTTDPP outputs a larger R L , favoring the formation of the face-on orientation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nevertheless, selenophene-based PBTSDPP exhibits a much larger L π of 38.51 Å than thiophene-based PBTTDPP with an L π of 18.01 Å, which can be attributed to the stronger Se−Se or Se−π interactions induced by the BTS units in PBTSDPP. 72,73 Larger L π from PBTSDPP yields a smaller R L , which leads to favorable edgeon orientation. Meanwhile, the smaller L π from PBTTDPP outputs a larger R L , favoring the formation of the face-on orientation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Currently, quantum chemical calculations and several spectroscopic techniques such as X-ray diffraction and NMR spectroscopy have been mainly used to investigate selenium-centered chalcogen bonds (SeChBs). These SeChBs mainly include Se ∙∙∙ N [ 47 , 48 , 49 , 50 , 51 , 52 ], Se ∙∙∙ O [ 10 , 13 , 47 , 51 , 53 , 54 ], Se ∙∙∙ S [ 47 , 55 ], Se ∙∙∙ Se [ 28 , 56 , 57 ], and Se ∙∙∙ π [ 58 , 59 , 60 ] contacts. Zhang [ 48 ], Mugesh [ 61 ], and Panda [ 11 ] and colleagues theoretically investigated the impacts of the substituents covalently bonded to the Se atom, hybridization of the nitrogen atom, the chelate ring, and rigidity on Se ∙∙∙ N ChBs.…”
Section: Introductionmentioning
confidence: 99%
“…Bauzá and colleagues [ 55 ] also demonstrated the significance of intermolecular Se ∙∙∙ O/S ChBs in the stabilization of protein–ligand complexes involving Se–pyranose through PDB surveys. Veljković et al [ 57 ] conducted a statistical analysis of crystallographic data from the Cambridge Structural Database (CSD), revealing the cooperative roles of Se ∙∙∙ Se ChBs and C/Se–H ∙∙∙ Se HBs in stabilizing crystal structures of organoselenium compounds. Tskhovrebov and coworkers [ 59 ] reported that symmetrical dimers of benzylic-substituted 1,2,4-selenodiazolium salts are stabilized through Se ∙∙∙ N and Se ∙∙∙ π ChBs, where the former are weaker than the latter.…”
Section: Introductionmentioning
confidence: 99%